INTEGRATION OF INDIAN PHILOSOPHY WITH BUDDHISM IN THE CONTEXT OF THE NOBLE EIGHTFOLD PATH - Lie, Nie; Kabri, Kabri; Vidya, Dama; Wigiartati, Wiwik (Jurnal Agama Buddha dan Ilmu Pengetahuan, 2024)
The Noble Eightfold Path is the core teaching of Buddhism that aims to guide individuals to nibbana. Indian philosophies, such as dharma and moksha, have a major influence on shaping Buddhist core values, creating a rich spiritual and ethical foundation. However, the integration of the two requires a deeper understanding to meet the challenges in the modern context. This study aims to explain the integration of Indian cultural philosophies with Buddhism in the context of the Noble Eightfold Path, and explore its impact on contemporary Buddhist practice. It uses a historical and philosophical approach through desk research to examine the influence of Veda values, including dharma, karma, and meditation practices, on the evolution of the essential elements of the Eightfold Path. The findings show that the integration of Indian cultural values ​​enriches the Noble Eightfold Path in terms of ethics, spirituality, and wisdom. Its relevance extends to cross-cultural contexts and addresses modern ethical challenges. The study concludes that the integration of Indian philosophies and Buddhism not only strengthens the foundation of Buddhist teachings but also creates a moral framework that is relevant to modern life.